Faktor-Faktor Yang Mempengaruhi Akseptor Kontrasepsi Tentang Minat Penggunaan Alat Kontrasepsi Dalam Rahim di Puskesmas Tahai - Anggraini, Ni Ketut Santia; Istiqomah, Istiqomah; Yulianti, Putri; Iswandari, Novita Dewi (JURNAL BIDANG ILMU KESEHATAN, 2025)
One of the efforts to make the Family Planning program a success is to provide quality services according to needs, including various types of contraception, one of which is the IUD. A mother's lack of interest in using the IUD contraceptive is thought to be influenced by several factors, including: The mother's level of education, knowledge, economics, culture, religion as well as people's ignorance about the IUD and people's ignorance about using it. One of the consequences of a mother's lack of interest in using IUD contraception is that other users often experience failure. Data obtained from the Pulang Pisau Regency BKKBN at the end of December 2022, the use of contraceptives by husband and wife couples consisted of contraceptive pills for 6,000 participants, injections for 11,482 participants, implants for 2,716 participants, IUDs for 211 participants, condoms for 1,375 participants, MOW for 400 participants and MOP for 6 participants. Method: Quantitative research with a cross-sectional approach, a population of 95 women of childbearing age with a minimum sampling technique of 30 WUS. Using univariate and bivariate analysis with chi square Results: Univariate analysis was obtained from 30 respondents aged 20-35 years (86.6%), multi/grande parity (73.4%), low education (83.4%) and respondents with high interest (70%). Bivariate analysis using chi square showed that age had an influence on interest with a p-value of 0.003, parity had an influence on interest with a p-value of 0.000, and education had an influence on interest with a p-value of 0.008. Conclusion: Age, parity and education factors influence contraceptive acceptors regarding their interest in using intrauterine contraceptives at the Tahai Community Health Center